Intelligent monitoring system of environmental biovariables in poultry farms. - Chiluisa Velasco, Gabriela Brillith (2020)
Modern technologies in poultry farming prevail over many limitations of traditional methods; thus they help reducing labor costs and increase productivity. In Ecuador, most poultry farms have modest systems capable of monitoring variations in temperature, humidity and gas concentrations caused by the generation of chicken manure in closed environments, which creates a stressful atmosphere affecting the health of broilers during breeding stage; therefore there is a palpable loss of money and productivity. This project presents an intelligent monitoring system composed of a star type sensor network for environmental monitoring variables in the poultry farm. Long Range Technology (LoRa) is used for the system communication, information is gathered and stored in a cloud database and then processed to be visualized through historical trends storage and alarm reporting creating an affordable and easy interpretable solution.